Trichromacy is insufficient for mate detection in a mimetic butterfly - Andrew Dang; Gary D. Bernard; Furong Yuan; Aide Macias-Muñoz; Ryan I. Hill; J. P. Lawrence; Aline Giselle Rangel Olguin; Armando Luis-Martínez; Sean P. Mullen; Jorge Llorente-Bousquets; Adriana D. Briscoe (Communications Biology)
Abstract Color vision is thought to play a key role in the evolution of animal coloration, while achromatic vision is rarely considered as a mechanism for species recognition. Here we test the hypothesis that brightness vision rather than color vision helps Adelpha fessonia butterflies identify potential mates while their co-mimetic wing coloration is indiscriminable to avian predators. We examine the trichromatic visual system of A. fessonia and characterize its photoreceptors using RNA-seq, eyeshine, epi-microspectrophotometry, and optophysiology. We model the discriminability of its wing color patches in relation to those of its co-mimic, A. basiloides, through A. fessonia and avian eyes. Visual modeling suggests that neither A. fessonia nor avian predators can readily distinguish the co-mimics’ coloration using chromatic or achromatic vision under natural conditions. These results suggest that mimetic colors are well-matched to visual systems to maintain mimicry, and that mate avoidance between these two look-alike species relies on other cues.